Pemetaan Implementasi Gerakan Literasi Sekolah Pada Tahap Pembiasaan Di Sekolah Dasar - Permana, Ai Triyaningsih Lina; Apriliya, Seni; Respati, Resa (LP2M Universitas Islam Ahmad Dahlan, 2025)
The implementation of the habituation stage of the School Literacy Movement (GLS) in elementary schools includes several aspects, including reading activities before the learning process begins which are carried out for 15 minutes, the availability of text-rich facilities and environments, the creation of a literacy environment, the selection of reading books, and active participation from the public. The purpose of this study is to summarize various findings related to the implementation, strategies, and impacts of the GLS habituation stage, especially at the elementary school level. This type of research is qualitative research with the Systematic Literature Review (SLR) method to examine the implementation of the habituation stage of the School Literacy Movement in elementary schools. The results of the study based on the Systematic Literature Review (SLR) have generally achieved all indicators of the habituation stage of the School Literacy Movement in elementary schools. However, there are still schools that are not optimal in their implementation. This is due to limitations in facilities that support literacy such as limitations in reading materials